Physical and Mathematical Fluid Mechanics - Scholle, Markus (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Fluid mechanics has emerged as a basic concept for nearly every field of technology. Despite a well-developed mathematical theory and available commercial software codes, the computation of solutions of the governing equations of motion is still challenging, especially due to the nonlinearity involved, and there are still open questions regarding the underlying physics of fluid flow, especially with respect to the continuum hypothesis and thermodynamic local equilibrium. The aim of this book is to reference recent advances in the field of fluid mechanics, both in terms of developing sophisticated mathematical methods for finding solutions to the equations of motion, on the one hand, and presenting novel approaches to the physical modeling, on the other hand. A wide range of topics is addressed, including general topics like formulations of the equations of motion in terms of conventional and potential fields; variational formulations, both deterministic and statistic, and their application to channel flows; vortex dynamics; flows through porous media; and also acoustic waves through porous media